Nutrient distribution and relationship with soil properties in different watersheds of Haryana - SAHOO, JYOTIRMAYA; DINESH, DINESH; BHAT, MOHAMMAD AMIN; ANIL, AJIN S; RAZA, MD BASIT (The Indian Journal of Agricultural Sciences, 2020)
Nutrient distribution in profile depths is unclear due to large exploitation of nutrient in the top soil while neglecting sub soil, which is also important from crop production point of view. Therefore, the present investigation was carried out in CCS Haryana Agricultural University, Hisar, Haryana, during 2017–18 where eight typical pedons (P) representing micro watersheds, viz. Motipura (P1), Sainiwas (P3), Jhumpa (P5), Budhsheli (P7), Motipura (P2), Sainiwas (P4), Jhumpa (P6) and Budhsheli (P8) were studied to evaluate the stratification of nutrients. A gradual decreasing pattern of macronutrient content was observed throughout the profile depths, which may be ascribed to accrual of organic matter in surface horizon by biological processes linked with natural vegetation. Nitrogen (N) was found to be low (42–189 kg/ha), phosphorous (P) low to medium (4.2–17.10 kg/ha), while potassium (K) and sulphur (S) were low to high, ranging between 62.2–326.5 kg/ha and 0.4–19 mg/kg, respectively. A positive and significant correlation was observed in case of N with P, K and S and among micronutrients, which implicates synergism among these nutrients. In general, the values of extractable micronutrients in the soils decreased irregularly down the profile.